2014
DOI: 10.1371/journal.pone.0110948
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End-Products Reduce Collagen Molecular Sliding to Affect Collagen Fibril Damage Mechanisms but Not Stiffness

Abstract: Advanced glycation end-products (AGE) contribute to age-related connective tissue damage and functional deficit. The documented association between AGE formation on collagens and the correlated progressive stiffening of tissues has widely been presumed causative, despite the lack of mechanistic understanding. The present study investigates precisely how AGEs affect mechanical function of the collagen fibril – the supramolecular functional load-bearing unit within most tissues. We employed synchrotron small-ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 59 publications
(99 reference statements)
7
96
3
1
Order By: Relevance
“…At the tissue level, ribose cross-linked specimens showed a clear loss of stress relaxation behavior, which is consistent with our previous studies [36,40] where AGEs were induced by methylglyoxal treatment, a substantially more reactive compound. This reduction in viscoelasticity can be attributed to changes at lower hierarchical levels, i.e.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…At the tissue level, ribose cross-linked specimens showed a clear loss of stress relaxation behavior, which is consistent with our previous studies [36,40] where AGEs were induced by methylglyoxal treatment, a substantially more reactive compound. This reduction in viscoelasticity can be attributed to changes at lower hierarchical levels, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Although the role of AGEs has been investigated mostly at the tissue level, a few studies reported AGE-related mechanical changes in collagen fibrils of tendon tissue. Our group [36] found a higher failure resistance in MGO treated collagen fibrils as well as a reduction in the lateral sliding of collagen molecules within fibrils, while fibril modulus remained unchanged. Svensson et al [21] observed a three-phase behavior pattern in the stress-strain curves of human collagen fibrils.…”
Section: Introductionmentioning
confidence: 48%
See 3 more Smart Citations